The Keeper: Vega Jane #2 - Baldacci, David (New York : Scholastic Press, 2015)
Vega Jane and her friend Delph have taken the map that Quentin Harris left them and set out from the town of Wormwood, determined to brave the Quag and find freedom on the other side--but the Quag was designed to keep the town people in, and it is filled with bloodthirsty creatures and sinister magic, and it is not going to let them escape unscathed.
Sequel to: The finisher.
Keywords: Magic -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Escapes -- Juvenile fiction; Fantasy; Adventure fiction